MOTIVATION AS A PSYCHOLOGICAL FACTOR IN THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF STUDENTS OF PEDAGOGICAL UNIVERSITIES - F. A. Rafiev (Galaxy International Interdisciplinary Research Journal, 2023)
The article examines the educational and professional motivation of students as an important component of professional competence, as well as psychological and pedagogical conditions and factors that contribute to the formation of motivation in the process of professional education